Finance for executives : managing for value creation - Hawawini, Gabriel A. (South-Western College, 1999)
This book is divided into five parts: Introduction to corporate finance; Evaluating financial performance; Making value-creating investment decisions; Making value-creating financing decisions; and Making value-creating business decisions.